Pengembangan Media Animasi Interaktif Pada Materi Laju Reaksi - Khaeruman, Khaeruman; Ahmadi, Ahmadi; Rehanun, Rehanun (IKIP Mataram, 2015)
Chemistry is a subject that considered as the difficult one by most of the students of senior high school since the characteristic of chemistry is microscopic that demanded the students to be able to understand the consept and then solve the problem .To help the student increasing their understanding .media is very needed. The media developed in this research is interactive Animation Media for the eleventh grade student and to test the teasibility level. The development modek used in his research is ADDIE (Analysis, design, develop, implement, evaluate). With some adaptation based on the development need. The resut of the development is interactive Animation Media in Reaction Rate Material which validation toward the result was done in two test, they are exoert test and limited group trial. There are 4 validators in this research, the are media expertise of FPMIPA IKIP Mataram and two chemistry teacher material expertise of MA NW Debok, and the subject of limited group test which was`a chemistry students an 10 students of MA NW Debok. The instment used to collect the data was questionnaire, while the data analysis by using everage percentage analysis the validation result of media expert shows that the average percentage analysis. The validation result of media expert shows that the average percentage was 76,25% and 75% which means valid/good. Validation done by the material expert shows that the average percentage was 86,25% and 91,25% which means good/valid, while the result of limited group test toword the students was 80,5% and toword the students was 87% which means that learning media which is interactive Animation Media in Reaction Rate Material is appropriate to use. It can be concluded that interactive Animation Media in Reaction Rate Material is appropriate to nuse by the teacher in teaching process.